2023
DOI: 10.1021/acs.jnatprod.2c01101
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aβ42 Aggregative Polyketides from the Antarctic Psychrophilic Fungus Pseudogymnoascus sp. OUCMDZ-3578

Abstract: Seven new polyketides, diphenyl ketone (1), diphenyl ketone glycosides (2−4), diphenyl ketone-diphenyl ether dimer (6), and anthraquinone-diphenyl ketone dimers (7 and 8), together with compound 5, were isolated from the psychrophilic fungus Pseudogymnoascus sp. OUCMDZ-3578 fermented at 16 °C and identified by spectroscopic analysis. The absolute configurations of 2−4 were determined by acid hydrolysis and 1-phenyl-3-methyl-5-pyrazolone precolumn derivatization. The configuration of 5 was first determined by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Alzheimer's disease (AD) is a major public health problem, affecting more than 20 million people worldwide. [20][21][22][23] The increased oxidative stress and decreased acetylcholine (ACh) were believed to be critical factors in the development of AD. [24][25][26][27] To establish the appropriate experimental concentration of the four compounds, a CCK-8 kit was adopted to detect the BV2 cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a major public health problem, affecting more than 20 million people worldwide. [20][21][22][23] The increased oxidative stress and decreased acetylcholine (ACh) were believed to be critical factors in the development of AD. [24][25][26][27] To establish the appropriate experimental concentration of the four compounds, a CCK-8 kit was adopted to detect the BV2 cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Fungi from the genus Pseudogymnoascus exhibit interesting capabilities in their specialized metabolism [15][16][17][18][19][20][21]. To gain a deeper understanding of Pseudogymnoascus' metabolic potential, molecular tools enabling its genetic manipulation are essential.…”
Section: Discussionmentioning
confidence: 99%
“…From a biotechnological perspective, numerous studies have demonstrated that extracts derived from diverse strains of Pseudogymnoascus harbor bioactive metabolites with antibacterial, antifungal, trypanocidal, herbicidal, and antitumoral properties [9][10][11][12][13][14]. Furthermore, chemical analyses of Pseudogymnoascus strains have revealed that members of this fungal genus produce different classes of compounds, such as sesquiterpenes [15], macrolides [16], polyketides [17,18], tetrapeptides [19], and various nitrogenous compounds [20,21]. This underscores the potential of Pseudogymnoascus as a prolific source of specialized metabolites.…”
Section: Introductionmentioning
confidence: 99%